2017
DOI: 10.1073/pnas.1705622114
|View full text |Cite
|
Sign up to set email alerts
|

Two transmembrane dimers of the bovine papillomavirus E5 oncoprotein clamp the PDGF β receptor in an active dimeric conformation

Abstract: The dimeric 44-residue E5 protein of bovine papillomavirus is the smallest known naturally occurring oncoprotein. This transmembrane protein binds to the transmembrane domain (TMD) of the platelet-derived growth factor β receptor (PDGFβR), causing dimerization and activation of the receptor. Here, we use Rosetta membrane modeling and all-atom molecular dynamics simulations in a membrane environment to develop a chemically detailed model of the E5 protein/PDGFβR complex. In this model, an active dimer of the PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Indeed, immunoblotting studies detected a dimeric conformation of the viral E5 protein in some organs of these lambs. This suggests that E5 protein was present as a dimer which is known to be the biologically active conformation of the protein 32 . To the authors’ knowledge, BPVs have not been previously reported as a cause of clinical disease in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, immunoblotting studies detected a dimeric conformation of the viral E5 protein in some organs of these lambs. This suggests that E5 protein was present as a dimer which is known to be the biologically active conformation of the protein 32 . To the authors’ knowledge, BPVs have not been previously reported as a cause of clinical disease in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…One critical function of BPV1 E5 is activation of the platelet-derived growth factor receptor (PDGFR), resulting in downstream mitogenic signalling, enhanced DNA synthesis and transformation [ 60, 61 ]. This occurs via direct binding of BPV1 E5 to the PDGFRβ isoform [ 62 ]. In contrast, there is no evidence for BPV4 E5 activation of growth-factor receptors; rather it disrupts the expression and activity of key cell-cycle regulators such as cyclin A and p27 KIP1 [ 63 ].…”
Section: The E5 Oncoproteinmentioning
confidence: 99%
“…In addition, foci of squamous epithelium composed of numerous cell layers on the internal surface of the amnion have been found to form the so-called amniotic plaques that are apparently normal ill-defined structures, whose physiological function, if any, is unknown [28]. Usually, definitive amniotic plaques are flat in appearance and vary in size from 2 to 4 mm in diameter [28,37]; their height can be up to 8 mm [29]. They have been described in white-tailed deer [37], in cows [38], and in ewes [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Similar levels of total PDGFR were detected in both six papillomatous and two grossly normal placentas, whereas there was a statistically significant (p  0.05) increase of phosphorylated PDGFR in papillomatous placentas compared to the samples of grossly normal placentas (Figure 8). As it has been shown that E5 dimerization is required for transforming activity via phosphorylation of the PDGFβR [29], an immunoblotting investigation to detect total and phosphorylated PDGFβR was also performed. Similar levels of total PDGFβR were detected in both six papillomatous and two grossly normal placentas, whereas there was a statistically significant (p ≤ 0.05) increase of phosphorylated PDGFβR in papillomatous placentas compared to the samples of grossly normal placentas (Figure 8).…”
Section: Virological Findingsmentioning
confidence: 99%
See 1 more Smart Citation